Organizational Citizenship Behavior in the Context of Public Administration: Implications for Organizational Performance and Human Resource Management - Risnawati, ‎; Ibrahim, Muh. Akmal; Hasniati, ‎ (KnE Social Sciences, 2025)
Organizational Citizenship Behavior (OCB) refers to voluntary behaviors exhibited by employees outside their formal duties, which positively contribute to the success and efficiency of the organization. This literature review aims to examine the factors influencing OCB, mediating variables, and their impact on organizations in the context of public administration. The review synthesizes research findings highlighting the influence of leadership, organizational commitment, organizational culture, and individual personality on OCB. Several studies have shown that transformational leadership and servant leadership have a significant impact on increasing OCB. Leaders who empower employees and pay attention to their needs tend to encourage them to behave more proactively in the organization, both in OCB-I (individual-directed citizenship behavior) and OCB-O (organization-directed citizenship behavior). Employees’ affective commitment to their organization plays an important role in encouraging their involvement in OCB. The higher the level of affective commitment, the more likely employees are to exhibit higher OCB. In addition, a supportive organizational culture, which emphasizes cooperation, trust, and open communication, can create an environment that encourages citizenship behavior among employees. However, several factors inhibit OCB, such as misattribution and loneliness at work. Misattribution reduces supervisors’ understanding of employees’ motivations behind OCB, while loneliness can hinder interpersonal relationships that are important for collaboration and OCB. Employee personality, particularly the openness dimension, has also been found to moderate the effects of misattribution on OCB. This review provides valuable insights for public organizations in managing leadership, commitment, and organizational culture to encourage OCB and improve organizational performance.